Contextualizing Taboo Words In Expressing Anger, Frustration, And Joke In The Horrible Bosses Movie - Widiastuti, Putu Yeni; Widiastuti, Ni Made Ayu; Rajeg, I Made (DAS Institute, 2025)
Taboo words are deeply shaped by the context of the situation, including the relationships between speakers and listeners, the topic being discussed, the setting, and the function of the conversation. This study focuses on the use of taboo words in Horrible Bosses movies, aiming to identify the types of taboo words used and to analyze their functions in expressing anger, frustration, and joke. The data for this research were collected using the documentation method, which involved note-taking. A checklist instrument was also used to help identify and collect specific dialogue adjacencies. The data analysis method employed in this study is descriptive qualitative. The research questions were addressed by applying the framework of taboo word types and functions proposed by Jay and the context of the situation proposed by Holmes, both of which fall under sociolinguistics theory. The findings show that taboo words are mainly used to express anger or frustration, especially in scenes involving unfair treatment or emotional outbursts. Some types of taboo words, such as epithets, cursing, profanity, slang, and insults or slurs, are closely tied to emotional release and conflict. Meanwhile, obscenity, vulgarity, and taboo appear in both serious and humorous contexts, depending on the context in which the taboo words are delivered. Additionally, scatology appears only in joking scenes. These patterns suggest that while some taboo word types only serve anger or frustration function, others are more flexible. Overall, the context plays a key role in shaping how and why taboo words are used in the movie. Keywords: taboo words, anger, frustration, joke, context of situation